Failure Mechanism and Acoustic Emission Precursors of Coal Samples considering Bedding Effect under Triaxial Unloading Condition - Rui Yang; Yan Zhou; Depeng Ma (Geofluids)
Bedding increases coal seam anisotropy, which leads to significant differences in the evolution laws of mining stress and strata movement. This work analyzed the dip angles of different layers to analyze the mechanical properties of the coal seam under unloading. The coal sample was subjected to triaxial compression and unloading damage acoustic emission testing. The brittleness characteristics of the coal sample failure in different bedding directions differed significantly. Compared with axial parallel bedding coal samples, axial vertical bedding and inclined stratification reached an ultimate strength. The stress–strain curve decreased sharply and showed visible brittle-drop characteristics. The average strengths of the axially inclined bedding and the parallel layered coal sample decreased compared with the axial vertical bedding coal sample and were 10.20 and 16.12 MPa, respectively, which implies a greater susceptibility to failure during unloading confining pressure tests. Acoustic emission monitoring indicated that the axial vertical bedding and inclined bedding showed sudden destruction of different coal samples, a reduction in axial parallel bedding ductility coal sample characteristics, and stronger unloading damage on the axis parallel to the bedding coal sample. Further, using the acoustic emission ring count rate and the cusp catastrophe theory, the unloading failure prediction of coal samples is carried out. The prediction results are not different from the experimental results, which shows that this method is feasible.